Effect of Remedial Teaching Using Curative Approach on Improvement of Student Learning Outcomes at Subject of Al-Qur'an Hadits in MTS Muhammadiyah Waru Baki Sukoharjo - Nur Ardiyansyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
This study aims to discuss how remedial teaching using curative approach in MTs. Muhammadiyah Waru Baki, Sukoharjo, how the student learning outcomes of Qur'an Hadits subjects in MTs. Muhammadiyah Waru Baki, Sukoharjo, and, whether there is any influence of remedial teaching using the curative approach in improving student learning outcomes of Qur'an Hadits subjects in MTs. Muhammadiyah Waru Baki, Sukoharjo. This research is quantitative. The research conducted by the researcher is also a causal nature of comparative research focused on comparing the free variables of some subjects who received a different influence of the independent variables in order to know the effect of remedial teaching using curative approach in improving the student learning outcomes in Qur'an Hadits subjects in MTs. Muhammadiyah Waru Baki, Sukoharjo, namely to test the hypothesis of data pairs using the formula t-test (sample paired t-test). Based on the mentioned problems above and after analysed, it can be concluded that (1) Implementation of remedial teaching in MTs. Muhammadiyah Waru Sukoharjo Baki is 71.9%, which means “good enough”. (2) The results of the students' learning experience increase 68.46% from the average value of 69.46 into 85.37 with a percentage increase of 23%. (3) From the calculation of normality test and paired sample t-test is resulted that arithmetic t> t table or 19.025 > 2.001 namely reject H0 and received H1, which means there are significant remedial teaching using curative approach to improve the student learning outcomes in Qur'an Hadits subjects in MTs. Muhammadiyah Waru Baki, Sukoharjo Keywords: Remedial, Curative and Learning Outcomes